A35 NEUTROPHIL ELASTASE PROTEOLYTIC ACTIVITY DRIVES A NOVEL PRO-RESOLUTION CELL MIGRATION PHENOTYPE. (15th March 2019) - Gordon, M; Dufour, A; MacNaughton, W
Abstract: Background: Neutrophils are the first immune cells recruited to areas of inflammation in inflammatory bowel disease (IBD) and sustained infiltration of activated neutrophils in inflamed tissue is a hallmark of disease. Neutrophils release high levels of reactive oxygen species and a variety of promiscuous proteases, including neutrophil elastase (NE), to destroy invading pathogens which can significantly damage the surrounding tissue. Elevated presence of uncontrolled proteases negatively contribute to the pathology of an inflammatory microenvironment. Neutrophils and their proteases are key players in the prelude to and resolution of inflammation. We have been studying how proteases can induce a switch in the colonic epithelium from a barrier to a repair phenotype during disrupted homeostasis via proteolytic processing of junctional proteins. Previously we have identified peptide fragments of E-cadherin generated by NE proteolysis which promote wound resolution independently of the full-length protein. Aims: We hypothesize that NE impacts wound resolution and tissue homeostasis through its proteolytic activity leading to the generation of bioactive peptide fragments. Methods: NE activity was determined using a fluorogenic substrate IV reporter and heat denaturation was used to inhibit the enzymatic activity of NE. Quantitative N-terminomics TAILS (Terminal amine isotopic labelling of substrates) was used to identify natural and neo-N-termini from IBD patients. Wound healing in Caco-2 cells was assayed using the IncuCyte™ live-cell imaging system with scratch wounds followed by exposure to 0.1- 500 ng/mL of NE. Results: We found an enrichment of neo-N-termini in inflamed IBD patient samples compared to healthy controls. Many proteins were identified to be differentially cleaved in IBD vs control tissues, suggesting altered proteolysis and a possible novel proteolytic post-translational signature contributing to epithelial homeostasis and resolution programming in the inflammatory milieu. Low-dose purified NE increased wound closure of CaCo2 monolayers in a concentration dependent manner with 1 ng/mL having the most significant effect (p<0.05). This effect was dependent upon NE proteolytic activity as the effect on wound healing was blocked with heat inactivation. These effects were determined to be due to an increased cellular migration program. Conclusions: We have previously shown a novel role for NE to process the adherens junction protein E-cadherin to generate peptide fragments with effects on epithelial function and now demonstrate that low levels of NE can be pro-resolution. Our data contribute to our understanding of the multi-axis signaling mechanisms underlying mucosal repair as regulated by innate immune cell proteases and suggests a new mechanisms of repair driving signaling that may be dysregulated during IBD and other chronic inflammatory diseases. Funding Agencies: CCC, CIHRUniversity Research Grants Committee (University of Calgary)